A multicriterial analysis of the efficiency of conservative information security systems - Dudykevych, Valeriy; Prokopyshyn, Ivan; Chekurin, Vasyl; Opirskyy, Ivan; Lakh, Yuriy; Kret, Taras; Ivanchenko, Yevheniia; Ivanchenko, Ihor (Eastern-European Journal of Enterprise Technologies, 2019)
The paper addresses the task on a multicriterial analysis of the effectiveness of conservative information security systems whose structure and components do not change over a certain period of time. The principal scheme of such systems includes a protected object, vulnerabilities ‒ channels for attacks, threats, and protection tools. Based on the assumption about the independence of attacks and protection tools, we have developed a discrete probabilistic model of damage to a protected object. For a random variable of the amount of damage over a fixed period of time, we have derived a representation in the form of a sum of binomially-distributed random variables, dependent on the parameters for attacks and protection. We have described in a similar manner the random variables for economic losses, recovery time, as well as recovery costs, for which mathematical expectations and variances have been obtained in the analytical form. To ensure the high statistical confidence, it has been proposed to determine the risk indicators using a Cantelli’s inequality. On this basis, we have defined performance indicators for a protection system, which characterize the probability of protected object’s safety, residual losses, conditionally saved costs, survivability, and the cost of recovery. By using a Pareto optimality theory, we have devised a procedure for multi-criteria analysis and rational design of conservative systems of information protection. Verification has been carried out for the audio information protection systems. A Pareto frontier has been investigated according to the criteria of economic benefit and investment costs for 66 variants of protection. We have examined the influence of protection level on the Cantelli’s measure for conditional savings, as well as the contribution of various types of protection devices to it. The research results have confirmed the saturation law by Gordon-Loeb for the case when over-protection does not improve the effectiveness of protection systems.